Peran Penting Masyarakat Dalam Pembangunan Desa di Desa Bangun Mulia Kecamatan Medan Amplas - R, Rostina (Yayasan Daarul Huda Kruengmane, 2025)
The most strategic poverty alleviation efforts in the era of regional autonomy can be formulated in one sentence i.e. “give opportunities to poor families and their communities to deal with their problems independently”. This means external parties must reposition their role, from agents of empowerment to facilitators of empowerment. The externally derived inputs into the empowerment process should refer fully to the needs and action designs made by the poor family itself together with its community through a productive process of dialogue to suit the local context. Local potential is the power, strength, willingness and capability that the village possesses to be able to develop in order to improve the welfare of the community. Both human resources and natural resources constitute the locally possessed potential as determining factors of the success of a rural development. Local potential in the form of human resources as a development subject knows the issues of the community itself while natural resources are wealth that are utilized to uplift the socio-economic well-being of rural communities. Community empowerment is essentially awakening the potential in individuals or groups by giving impetus, raising awareness of the potential of the person or group with the aim of empowerment leading to a state of achievement or desired direction of change in the society that is socially empowered and useful. economics of its society. Rural community development constitutes an important part of the realization of the development of regional autonomy in order to level the development and welfare of the community. One of the efforts made by the government is to increase the participation of rural communities by making national programs one of which is the Rural Community Empowerment Programme. As we know, rural society is a society synonymous with poverty and backwardness while no less potential is possessed by rural society.